Role of CBNAAT in Diagnosing of Extra-Pulmonary Tuberculosis at a Tertiary Care Centre in a City of Karnataka: A Cross Sectional Study (Indian Journal of Public Health Research & Development, 2023)
Background: Cartridge based nucleic acid amplification test(CBNAAT) detects the presence of TB bacilli and also Rifampicin susceptibility.This test is currentlyrecommended as a ‘‘first line’’ fast diagnostic test inhigh TB burden countries like India.Aim & Objective: 1. To assess the yield of CBNAAT in detecting extra-pulmonary tuberculosis for patient attending S.S.I.M.S & RC, Davanagere.2. To assess the Rifampicin susceptibility in samples of presumptive extra-pulmonary TB patients using CBNAAT.Settings and Design: Cross sectional study was conducted among the patients after screening them with symptoms suggestive of extra-pulmonary TB coming to S. S.I.M.S & RC. Davangere.Methods and Material: 107 samples were collected and subjected to CBNAAT for detection of Mycobacterium tuberculosis and Rifampicin Susceptibility.Statistical analysis used: chi square test was applied to find out the association between Extra-pulmonary Tuberculosis with demographiccharacteristics and to find out the association between CBNAAT with demographic characteristics.Results: The yield of CBNAAT was of sensitivity of 100%, specificity of 98.7%, Positive predictive value (PPV) of 96.9%, Negative predictive value(NPV) was 100% and Accuracy was 99.1%.Conclusions: This study reinforces the importance of CBNAAT which has an impact on early detection, treatment and outcome of Extra-pulmonary Tuberculosis.
Keywords: : Extra-pulmonary Tuberculosis, CBNAAT, Davanagere.